Multidose prophylactic IV antibiotics do not lower the risk of surgical site infection for isolated closed ankle fractures. Issue 4 (December 2019) - Frank, Matt; Francis, Jeffrey; Bender, Mark; Roberts, Michael; Watson, David; Shah, Anjan; Maxson, Ben; Infante, Anthony; Sanders, Roy; Mir, Hassan R.
Abstract: Objectives: To compare the surgical site infection (SSI) rates in ankle fracture patients receiving either single preoperative intravenous (IV) dose (SD) or multidose 24 hours IV postoperative (MD) perioperative IV antibiotic prophylaxis. Design: Retrospective case–control study. Setting: Level I Trauma Center. Patients/Participants: Three hundred fourteen patients with isolated ankle fractures, OTA classifications 44A1-3, 44B1-3, and 44C1-3, who presented to our institution between January 2012 and June 2016. Intervention: Operative fracture fixation with either the administration of SD or MD perioperative IV antibiotic prophylaxis. Main outcome measurements: SSI. Results: Three hundred fourteen patients met all study criteria. There were 99 patients in the SD group with a mean age of 44.2 years and 215 patients in the MD group with a mean age of 47.7 years. The overall SSI rate was 5.1% in the SD group versus 2.8% in the MD group ( P = .312). The superficial SSI rate was 2.0% in the SD group versus 1.4% in the MD group not significant (NS). The deep SSI rate was 3.0% in the SD group versus 1.4% in the MD group (NS). Conclusion: The SSI rates in isolated closed ankle fractures receiving either SD or MD perioperative IV antibiotic prophylaxis were similar. Further studies should be considered to help guide the standard of care for perioperative IV antibiotic prophylaxis. Level of evidence: Therapeutic Level III retrospective case–control study.